2017
DOI: 10.1080/14767058.2017.1315666
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the five minute Apgar score, mode of birth and neonatal outcomes

Abstract: Objective: To investigate the relationship between the five-minute Apgar score categories (low, intermediate, and normal), mode of birth and neonatal outcomes. Methods: This was a retrospective cross sectional study of term singleton deliveries at Mater Mothers' Hospital in Brisbane, Australia between January 2007 and December 2015. The five minute score was subdivided in to three categories -low (0-3), intermediate (4-6), and normal (7). These were correlated with adverse neonatal outcomes and mode of birth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 28 publications
5
36
1
2
Order By: Relevance
“…A total of 382,518 neonates were assessed in 16 studies; of those, 327,272 were neonates born by vaginal delivery and the rest (55,246) were by ECS. Except for three (9)(10)(11), all the studies showed that the incidence of respiratory morbidity was high in ECS (8,(12)(13)(14)(16)(17)(18)(19)(20)(21)(22)(23)(24). In particular, two studies showed that the risk of neonatal respiratory morbidity was 12.35 and 10 times more in neonates born by ECS (RR = 12.35; 95% CI: 0.66-222.…”
Section: Respiratory Morbidity and Mode Of Deliverymentioning
confidence: 99%
“…A total of 382,518 neonates were assessed in 16 studies; of those, 327,272 were neonates born by vaginal delivery and the rest (55,246) were by ECS. Except for three (9)(10)(11), all the studies showed that the incidence of respiratory morbidity was high in ECS (8,(12)(13)(14)(16)(17)(18)(19)(20)(21)(22)(23)(24). In particular, two studies showed that the risk of neonatal respiratory morbidity was 12.35 and 10 times more in neonates born by ECS (RR = 12.35; 95% CI: 0.66-222.…”
Section: Respiratory Morbidity and Mode Of Deliverymentioning
confidence: 99%
“…Nevertheless, there are professionals involved in childbirth care that try to reduce the duration of the second stage by obstetric interventionism in order to avoid neonatal complications. Paradoxically, these interventions, such as immediate pushing (initiated as soon as complete dilation is identified) [7], instrumental birth [8] or fundal pressure [9], may themselves increase the risk of neonatal morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…We set the cut-off value as an Apgar score 7, because neonatal complications including respiratory distress, feeding problems, hypothermia, and seizures are all significantly associated with the Apgar score lower than 7 (ref. 11,14 ). We recorded significant difference in Apgar scores of the 1, 5 and 10 min in groups of GA and RA, preferring RA.…”
Section: Discussionmentioning
confidence: 73%